IFN-γ down-regulates the PD-1 expression and assist nivolumab in PD-1-blockade effect on CD8+ T-lymphocytes in pancreatic cancer - Guoping Ding; Tao Shen; Chen Yan; Mingjie Zhang; Zhengrong Wu; Liping Cao (BMC Cancer, 2019)
Abstract Background Pancreatic cancer is characterized by a highly immunosuppressive tumor microenvironment and evasion of immune surveillance. Although programmed cell death 1 receptor (PD-1) blockade has achieved certain success in immunogenic cancers, the responses to the PD-1 antibody are not effective or sustained in patients with pancreatic cancer. Methods Firstly, PD-1 expressions on peripheral CD8+ T-lymphocytes of patients with pancreatic cancer and healthy donors were measured. In in vitro study, peripheral T-lymphocytes were isolated and treated with nivolumab and/or interferon-γ, and next, PD-1-blockade effects, proliferations, cytokine secretions and cytotoxic activities were tested after different treatments. In in vivo study, mice bearing subcutaneous pancreatic cancer cell lines were treated with induced T-lymphocytes and tumor sizes were measured. Results PD-1 protein expression is increased on peripheral CD8+ T cells in patients with pancreatic ductal adenocarcinoma compared with that in health donor. PD-1 expression on CD8+ T-lymphocytes was decreased by nivolumab in a concentration-dependent manner in vitro. IFN-γ could directly down-regulate expression of PD-1 in vitro. Furthermore, the combination therapy of nivolumab and IFN-γ resulted in greatest effect of PD-1-blockde (1.73 ± 0.78), compared with IFN-γ along (18.63 ± 0.82) and nivolumab along (13.65 ± 1.22). Moreover, the effects of nivolumab plus IFN-γ largest promoted the T-lymphocytes function of proliferations, cytokine secretions and cytotoxic activities. Most importantly, T-lymphocytes induced by nivolumab plus IFN-γ presented the best repression of tumor growth. Conclusions IFN-γ plus a PD-1-blockading agent could enhance the immunologic function and might play a crucial role in effective adoptive transfer treatments of pancreatic cancer.